Nanozinc and plant growth-promoting bacteria improve biochemical and metabolic attributes of maize in tropical Cerrado - Jalal, Arshad; Oliveira, Carlos Eduardo da Silva; Bastos, Andréa de Castro; Fernandes, Guilherme Carlos; de Lima, Bruno Horschut; Furlani Junior, Enes; de Carvalho, Pedro Henrique Gomes; Galindo, Fernando Shintate; Gato, Isabela Martins Bueno; Teixeira Filho, Marcelo Carvalho Minhoto (Frontiers in Plant Science, 2023)
Plant growth-promoting bacteria (PGPBs) could be adapted as a sustainable strategy to promote plant growth and yield to feed ever growing global population with nutritious food. Foliar application of nano zinc oxide (ZnO) is one of environmentally safe strategy that alleviate Zn malnutrition by improving biochemical attributes and storage proteins of grains. In this context, the current study aimed to investigate the combined effect of seed inoculation with PGPBs and foliar nano ZnO application on growth, biochemical, nutrient metabolism, and yield of maize in tropical savannah of Brazil. The treatments were consisted of four PGPBs inoculations (without inoculation, Azospirillum brasilense, Bacillus subtilis, Pseudomonas fluorescens, applied by seeds) and two doses of Zn (0 and 3 kg ha−1, applied from nano ZnO in two splits by leaf). Inoculation of B. subtilis with foliar ZnO application increased shoot dry matter (7.3 and 9.8%) and grain yield (17.1 and 16.7%) in 2019-20 and 2020-2021 crop seasons respectively. Inoculation with A. brasilense increased 100-grains weight by 9.5% in both crop seasons. Shoot Zn accumulation was improved by 30 and 51% with inoculation of P. fluorescens in 2019-20 and 2020-2021 crop seasons. Whereas grain Zn accumulation was improved by 49 and 50.7% with inoculation of B. subtilis and P. fluorescens respectively. In addition, biochemical attributes (chlorophyll a, b and total, carotenoids, total soluble sugar and amino acids) were improved with inoculation of B. subtilis along with foliar nano ZnO application as compared to other treatments. Co-application of P. fluorescens with foliar ZnO improved concentration of grains albumin (20 and 13%) and globulin (39 and 30%). Also, co-application of B. subtilis and foliar ZnO improved concentration of grains glutelin (8.8 and 8.7%) and prolamin (15 and 21%) in first and second seasons. Therefore, inoculation of B. subtilis and P. fluorescens with foliar nano ZnO application is considered a sustainable and environmental safe strategy for improving biochemical, metabolic, nutritious and productivity attributes of maize in tropical savannah regions.